Kebugaran Jasmani Mahasiswa Pendidikan Guru Sekolah Dasar dalam Kajian Teori dan Praktik Matakuliah Penjas SD - Al Wahid , Sucahyo Mas’an; Kartini, Kartini; Antonio, Antonio (Jurnal Porkes, 2024)
The purpose of this study is the lack of physical activity because learning is carried out hybridly in 2020 to 2022, while in 2017 to 2019 the implementation of face-to-face student learning. The research method uses qualitative with a description method that describes the physical activity of elementary school physical education courses in physical fitness material from 2017 to 2022 with the subject of 1 class each generation. The results of the study were achievements in the short distance running category (LJP) 80% dominant in the maximum number, namely 5 points with a total number of 37 testees, achievements in the push up category (PUSH) 60% hybrid pattern and 75% face-to-face pattern, in the sit up category (SIT) 30% of the increase in numbers was dominated by men in hybrid patterns and 40% face-to-face patterns, in the vertical jump (VJ) category 85% of testees obtained maximum points in face-to-face patterns and 76% hybrid patterns, and in the long distance running category (LJM) 50% met the criteria in hybrid patterns and 61% in face-to-face patterns. It can be concluded that the Indonesian Physical Fitness Measurement Test conducted through a hybrid with teaching and supervision methods through project-based learning with the acquisition of sufficient categories has an impact on some students, while the overall face-to-face is good because there are corrections to the implementation of physical fitness tests.